VALIDATING CORE CONCEPTS OF CYBERSECURITY CONTROL USING COMMONLY ACCEPTED STANDARDS. Issue 5 (4th May 2019) - Shoemaker, Dan; Kohnke, Anne; Sigler, Ken
ABSTRACT: Expert models specify repeatable actions that are designed to ensure an organization's resources are utilized for maximum effectiveness. Therefore, a commonly accepted expert model can serve as the basis for defining and enforcing a satisfactory degree of cybersecurity for any organization. In that respect then, expert models serve as a fixed point of reference for instituting specific cybersecurity control. This paper discusses the evolution of cybersecurity expert models, core knowledge elements, and the areas of agreement between the common expert models.